Implementasi pelatihan pendekatan STREAM berbasis project based learning dalam kurikulum pendidikan anak usia dini - Leli Halimah; Mirawati Mirawati; Maya Purnama Sari; Ayu Hopiani (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2022)
There are so many advantages of the PBL-based STREAM approach if it is implemented in the ECE curriculum. However, no matter how great a learning approach is, without a well-understood teacher regarding its theoretical basis and how to apply it, then this approach will not give any meaning. For this reason, teachers see the need to receive training so that they are skilled in applying the STREAM-PBL approach to the PAUD curriculum. This training is a form of community service which is carried out in a blended way through online meetings using zoom meetings and offline meetings. The purpose of this training is to provide insight and skills related to the implementation of the STREAM-PBL approach in the PAUD curriculum. This training was attended by PAUD teachers who became partners in the implementation of PPLSP and the tri dharma of the UPI Campus PGPAUD study program in Cibiru. The results of this training activity indicate an increase in teachers' understanding regarding the implementation of the STREAM-PBL approach in the PAUD curriculum. Teachers believe that the STREAM-PBL approach has great potential to stimulate children's creativity and other aspects of development.